Evaluating In-Service Education: Teacher Effectiveness and Attitude Changes among Odisha Elementary Teachers - Suchitra Dash; Kulamani Sahoo (RADINKA JAYA UTAMA PUBLISHER, PADANG< INDONESIA, 2026)
This study investigates the role of in-service education programmes in enhancing teacher effectiveness and shaping attitudes toward the teaching profession among elementary teachers in Odisha, India. Employing a quasi-experimental pre-test/post-test design with a control group, the study compared two groups of elementary teachers (trained group, n = 30, control group, n = 30). Data were collected using the Teacher Effectiveness Scale (TES) and the Attitude toward Profession Inventory (ATPI), both validated and reliable instruments. The results revealed that the trained group demonstrated significant improvements in teacher effectiveness (p<.05), particularly in planning, classroom management, and student assessment subdomains, with medium-to-large effect sizes (Cohen’s d = 0.45–0.70). Additionally, teacher attitudes toward the profession improved moderately, with gains in job satisfaction and professional commitment. The findings underscore the value of in-service education as a mechanism for enhancing instructional quality and strengthening professional identity. The study concludes by highlighting implications for policy, practice, and future research to ensure sustained quality in elementary education.